Biogas Upgrading - Sirichai Koonaphapdeelert (2020)
© 2020, Springer Nature Singapore Pte Ltd. Many end use applications require a high quality of biogas, which means the gas must contain a higher percentage of methane than found in raw biogas. In such situations, it is common to improve the quality of the biogas by reducing the contaminants and unwanted gases. Contaminants, in this case, are defined as any substances that are not methane. For example, if used in natural gas vehicles, the raw biogas heating value should increase from to Upgrading involves two key steps, biogas cleaning, which is a pretreatment process readying the gas for the second process. This second process, calling upgrading, purifies the low methane, high carbon dioxide biogas into high methane, low carbon dioxide—biomethane.